A vibroacoustic model of a reduction line of a gas installation - Zbigniew ENGEL; Ryszard PANUSZKA; Mieczysław MENŻYŃSKI (Archives of Acoustics)
This paper proposes a method for predicting the sound power level of a reduction line of a gas installation, based on a vibroacoustic cylindrical equivalent model. This model was verified experimentally on a real object. It permits approximate prediction of the sound power level of a reduction line, depending on its technological and structural parameters, particularly for medium and high frequencies.